Estrutura de platô na magnetização em modelos de spins frustrados - Anjos, Rosana Aparecida dos (Universidade Federal de São Carlos, 2012)
This thesis study the phase transition, forms classical and quantum models of spin frustration. The Heisenberg model of spin 1/2 with exchange anisotropy with competitive interactions between first (J1) and second (J2) neighbors, called Model J1 − J2, will be analyzed through phase diagrams where we consider several parameters, including the frustration J2 and J1 what is the delimiter between the Ising and Heisenberg models. The Ising model is also studied in this work. We apply effective field theory (EFT) in finite clusters via differential operator technique (TOD). In particular starting phase diagrams of these models allowed us to observe the state antiferromagnetic (AF) and SAF called collinear (CAF), formed by horizontal lines (vertical) and ferromagnetic oriented along the vertical direction (horizontal) chains are oriented antiparalelo and a second stage still called SAF or (CAF-1) having alternate rows in ferromagnetic and antiferromagnetic. A special brackets is made for one phase called SAF-2 or CAF-2, comprised two consecutive columns ferromagnetic and antiferromagnetic next and so on, thereby constructing a new phase. With the application of the external field we had a phenomenon capable of generating structures in plateau magnetization. The plateau phenomenon is influenced by the frustration parameter _ = J2/J1, the plateau were studied for the Ising and Heisenberg models generate different results with satisfactory conclusion. The methods and models were applied to networks in two and three dimensions.
Keywords: Física da matéria condensada; Spin; Platô; Magnetização; CIENCIAS EXATAS E DA TERRA::FISICA